C/EBPβ deletion in oncogenic Ras skin tumors is a synthetic lethal event. Issue 11 (November 2018) - Messenger, Zachary; Hall, Jonathan; Jima, Dereje; House, John; Tam, Hann; Tokarz, Debra; Smart, Robert
Abstract Therapeutic targeting of specific genetic changes in cancer has proven to be an effective therapy and the concept of synthetic lethality has emerged. CCAAT/enhancer-binding protein-β (C/EBPβ), a basic leucine zipper transcription factor, has important roles in cellular processes including differentiation, inflammation, survival, and energy metabolism. Using a genetically engineered mouse model, we report that the deletion C/EBPβ in pre-existing oncogenic Ha-Ras mouse skin tumors in vivo resulted in rapid tumor regression. Regressing tumors exhibited elevated levels of apoptosis and p53 protein/activity, while adjacent C/EBPβ-deleted skin did not. These results indicate that the deletion of C/EBPβ de-represses p53 in oncogenic Ras tumors but not in normal wild-type Ras keratinocytes, and that C/EBPβ is essential for survival of oncogenic Ras tumors. Co-deletion of C/EBPβ and p53 in oncogenic Ras tumors showed p53 is required for tumor regression and elevated apoptosis. In tumors, loss of a pathway that confers adaptability to a stress phenotype of cancer/tumorigenesis, such as DNA damage, could result in selective tumor cell killing. Our results show that oncogenic Ras tumors display a significant DNA damage/replicative stress phenotype and these tumors have acquired a dependence on C/EBPβ for their survival. RNAseq data analysis of regressing tumors deleted of C/EBPβ indicates a novel interface between p53, type-1 interferon response, and death receptor pathways, which function in concert to produce activation of extrinsic apoptosis pathways. In summary, the deletion of C/EBPβ in oncogenic Ras skin tumors is a synthetic lethal event, making it a promising target for future potential anticancer therapies.